Polyphenol-Rich Propolis Extracts Strengthen Intestinal Barrier Function by Activating AMPK and ERK Signaling - Kai Wang (Nutrients, 2016)
Propolis has abundant polyphenolic constituents and is used widely as a health/functional food. Here, we investigated the effects of polyphenol-rich propolis extracts (PPE) on intestinal barrier function in human intestinal epithelial Caco-2 cells, as well as in rats. In Caco-2 cells, PPE increased transepithelial electrical resistance and decreased lucifer yellow flux. PPE-treated cells showed increased expression of the tight junction (TJ) loci occludin and zona occludens (ZO)-1. Confocal microscopy showed organized expressions in proteins related to TJ assembly, i.e., occludin and ZO-1, in response to PPE. Furthermore, PPE led to the activation of AMPK, ERK1/2, p38, and Akt. Using selective inhibitors, we found that the positive effects of PPE on barrier function were abolished in cells in which AMPK and ERK1/2 signaling were inhibited. Moreover, rats fed a diet supplemented with PPE (0.3% in the diet) exhibited increased colonic epithelium ZO-1 expression. Overall, these data suggest that PPE strengthens intestinal barrier function by activating AMPK and ERK signaling and provide novel insights into the potential application of propolis for human gut health.